Head and neck squamous cell carcinoma epidemiology at diagnosis: A description of public and private health care systems in Brazil regarding tumor location, staging and risk factors - Heloisa Arantes; Diego Chaves Rezende Morais; Maria Aparecida do Carmo Rego; Paula de Mendonça Batista; Cicera Pimenta Marcelino; Milena Falcão Almeida; Marion Coting Braga; Paula Cristina Pungartnik; Angelica Carreira dos Santos; Juliana Ominelli; Tharcísio Machado Coelho; Fernanda Bohns Pruski Ramos; et al. (Oral Oncology Reports)
Objectives: There is a limited number of updated epidemiological Brazilian data on head and neck squamous cell carcinoma (HNSCC). This study aimed to describe demographic and clinical characteristics of HNSCC patients from Brazilian public and private systems. Methods: This is a retrospective observational study that included patients diagnosed with HNSCC from Brazilian public and private settings from 2016 to 2018. As for the public scenario, data were drawn from the public hospital national cancer registry database. As for the private sector, the data were extracted from medical records of patients from Oncoclinicas, a large Brazilian oncology group. Results: A total of 37,121 patients were included in the study, with 36,914 from the public and 207 from the private system. Patients in the public sector were younger than those in the private sector, with medians ages of 61.2 and 66.9 years, respectively. In both cohorts, a predominance of men with a history of tobacco and alcohol consumption and an advanced locoregional stage at diagnosis was observed. The main site of the primary tumor was the oropharynx in the private sector and oral cavity in the public sector. Among patients with oropharyngeal cancer, only those in the private sector were tested for HPV, with the majority being positive. Conclusions: This real-world data study provides epidemiologic characteristics of patients with HNSCC in two different Brazilian healthcare settings, presenting relevant insights into possible opportunities for improvements in the patient's journey with HNSCC.